Developing English Comic Strips to Teach Reading for Ten Grade Students at Vocational High School IT Baitunnur Punggur - Rama Pramudya, Galang; Suhono, Suhono; Zuniati, Mai (CV. Creative Tugu Pena, 2024)
This article analyzed how the development of English comic strips for teaching reading grade X Vocational High School (SMK) IT Baitunnur Punggur and to find out the difference in student learning outcomes before and after teachers use English comic strips to teach reading grade X SMK IT Baitunnur Punggur. This research was conducted in the tenth grade of the second semester at SMK IT Baitunnur Punggur. The researchersd used Research and Development (R&D). In this case, the research only resulted in a product design, which was internally verified using the opinions of experts and practitioners and did not lead to the production of goods on a global scale. The pre-test and post-test resulted of the developed product, as well as the validation findings by a group of media experts, material experts, and students, were considered valid. Based on the validation results from two lecturers and two teachers, as well as material experts and media experts, the percentage of feasibility assessment with